Schematizing gender-specific vulnerability perceptions and adaptation strategies on volcanic smog-affecteted communities the case of farmers and fishers in Laurel, Batangas, the Philippines - Gagarin, Wesley S.; Banquiles, Nyssa Mae T. (2024)
Disasters impact men and women differently. The Philippines, located in the Pacific Ring of Fire, has 24 active volcanoes and is highly susceptible to volcanic eruptions. These eruptions produce volcanic smog (vog), which affects the health and livelihoods of both men and women. This study uses the participatory rural approach to examine the gender-specific vulnerabilities, capacities, and hazard perceptions of eight male and nine female farmers and fishers in Barangay Gulod, Laurel, Batangas, the Philippines, regarding vog from Taal Volcano. Barangay Gulod was chosen due to its proximity and high susceptibility to Taal's eruptions. The findings reveal that vog adversely affects the health and livelihoods of both male and female participants. Female vulnerability is further influenced by unsafe housing structures and their multiple economic, domestic, and caregiving roles during vog events. Both genders reported that their lack of information on mitigating the impacts of vog increased their vulnerability. However, strong social and organizational support enhances their capacity to cope with and recover from the health and economic impacts of vog.
The study provides valuable insights for developing gender-based strategies in local disaster risk reduction and vog management for the municipality of Laurel, Batangas, the Philippines.
Keywords: Volcanism; Volcanic hazard analysis